(untitled) (ENTHYMEMA, 2015)
Religious, in particularly Christian imagery, was ubiquitous in Leningrad samizdat poetry of the 1970s. This essay addresses two main questions that are closely related: is the term «religious verse» appropriate for this kind of poetry; how are we to define «religious» in this case? Secondly, what were the common denominators of religious verse in 1970s Leningrad.